Cultural sociology of mental illness : an A-to-Z guide - Scull, Andrew, 1946- (Thousand Oaks : SAGE Reference, 2014)
Expert scholars explore the culture of mental illness from the non-clinical perspectives of sociology, history, psychology, epidemiology, economics, public health policy, and finally, the mental health patients themselves. Key themes include cultural comparisons of mental health disorders; cultural sociology of mental illness around the world; economics; epidemiology; mental health practitioners; non-drug treatments; patient, the psychiatry, and psychology; psychiatry and space; psychopharmacology; public policy; social history; and sociology.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Psychology, Pathological -- Cross-cultural studies; Mental illness -- Social aspects -- History; Cultural psychiatry; Mentally ill -- Care -- Social aspects